Process for reducing magnetic substances in battery-grade lithium carbonate

A multi-step process for producing battery-grade lithium carbonate addresses equipment blockage and impurity issues by using advanced filtration, electro-driven separation, and demagnetization techniques, achieving high purity and efficient production with reduced environmental impact.

CN119118165APending Publication Date: 2024-12-13QINGHAI DONGTAI JINEL LITHIUM RESOURCES CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411181005.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing filtration and separation processes in the production of battery-grade lithium carbonate are prone to equipment blockage and membrane fouling, leading to impurities such as silt, suspended matter, colloidal substances, and magnetic substances, which affect the purity and safety of lithium batteries.

Method used

A multi-step process involving inclined plate sedimentation, multi-media filtration, electro-driven membrane magnesium-lithium separation, refining reaction with sodium hydroxide and barium chloride, lithium carbonate conversion crystallization, and multi-stage demagnetization treatment, including high-gradient magnetic separation, to reduce magnetic substances in lithium carbonate.

Benefits of technology

The process effectively removes impurities, ensuring high purity and consistency of lithium carbonate, improving production efficiency and safety, while minimizing environmental impact and reducing equipment maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118165A_ABST
    Figure CN119118165A_ABST
Patent Text Reader

Abstract

The invention discloses a process for reducing magnetic substances in battery grade lithium carbonate, and relates to the technical field of lithium battery materials, in particular to a process for reducing magnetic substances in battery grade lithium carbonate, which comprises the following steps: pretreatment of brine, inclined plate sedimentation, plate-and-frame pressure filtration, multi-medium filtration and security filtration; performing magnesium-lithium separation through an electric driving membrane, and performing high-efficiency lithium-magnesium separation through an ion selective electric driving membrane; refining reaction: deeply removing calcium, magnesium and sulfate ions by adopting sodium hydroxide and barium chloride solution; lithium carbonate is converted into crystals, and the crystals are converted through a sodium carbonate solution; demagnetizing treatment: reducing the content of magnetic substances in the lithium carbonate through a multi-section and multi-stage demagnetizing process; and crushing the product, and controlling the particle size of lithium carbonate through airflow crushing equipment. Various impurities, including silt, suspended solids, colloidal substances and magnetic substances, in the raw material brine are effectively removed through an optimized multi-layer filtering technology, ion selective electrically-driven membrane separation, a refining reaction and a multi-stage demagnetizing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery materials, and in particular to a process for reducing magnetic substances in battery-grade lithium carbonate. Background Art

[0002] Battery-grade lithium carbonate is one of the raw materials for producing lithium batteries. It is mainly used to prepare lithium-ion battery positive electrode materials such as lithium cobalt oxide, lithium manganese oxide, ternary materials and lithium iron phosphate. When magnetic substances exist in the positive electrode materials, such as Fe, Cr and Zn, it will cause battery self-discharge, bulging, and even short circuit and explosion. The higher the content of magnetic substances in the lithium battery, the greater its self-discharge rate. In the field of lithium battery material manufacturing, battery-grade lithium carbonate is an important raw material for lithium batteries. Its purity and quality directly affect the performance and safety of the battery.

[0003] In the prior art, after the initial treatment of salt lake brine, a large amount of mud, suspended matter, colloidal substances and magnetic substances often remain. These impurities not only affect the purity of lithium carbonate, but also form crystal dendrites during the use of the battery, leading to safety hazards such as battery short circuit and fire.

[0004] Due to design limitations, traditional filtration and separation processes are prone to equipment blockage and membrane fouling, which in turn affects production efficiency and stability. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a process for reducing magnetic substances in battery-grade lithium carbonate, which solves the problem in the prior art that after preliminary treatment of salt lake brine, a large amount of silt, suspended matter, colloidal substances and magnetic substances often remain, affecting the purity of lithium carbonate.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A process for reducing magnetic substances in battery-grade lithium carbonate, comprising the following steps: The pretreatment of brine adopts inclined plate sedimentation, plate and frame filter press, multi-media filtration and security filtration; Electro-driven membrane magnesium-lithium separation, efficient lithium-magnesium separation through ion-selective electro-driven membrane; Refining reaction, using sodium hydroxide and barium chloride solution to deeply remove calcium, magnesium and sulfate ions; Lithium carbonate conversion crystallization, through sodium carbonate solution conversion crystallization; Demagnetization treatment, using a multi-stage and multi-level demagnetization process to reduce the content of magnetic substances in lithium carbonate; The product is crushed and the particle size of lithium carbonate is controlled by air flow crushing equipment.

[0007] Preferably, the brine pretreatment step comprises: Reduce brine turbidity to 1NTU-1.2NTU through inclined plate and inclined tube sedimentation; The brine turbidity is further reduced through plate and frame filtration, multi-media filtration and security filtration.

[0008] Specifically, the filtration pressure of the plate and frame filter press is 0.5MPa, the filter material layers of the multi-media filter include coarse sand (particle size 1mm-2mm), fine sand (particle size 0.5mm-1mm) and anthracite (particle size 0.8mm-1.2mm), and the security filter adopts PP filter element with a filtration accuracy of 5μm.

[0009] Preferably, the electrically driven membrane magnesium-lithium separation step adopts an imported large flow channel ion exchange membrane stack, and optimizes the combination of partitions in the membrane stack to make the lithium recovery rate of magnesium-lithium separation ≥80%.

[0010] Specifically, the flow channel width of the ion exchange membrane stack is 1 mm, the partition thickness is 0.3 mm, and the membrane stack material is a polymer material with high anti-pollution performance. The optimized membrane stack combination can reduce compartment blockage and membrane pollution.

[0011] Preferably, the refining reaction step comprises: Magnesium ion precipitation was performed using 30% sodium hydroxide solution at 50°C-60°C; Sulfate ion precipitation was performed using 30% barium chloride solution; After circulating filtration through the plate and frame filter press, it is filtered through a precision filter and the acid is adjusted to a pH value of 6-7. The filtration pressure range of the plate and frame filter press is 0.3MPa-0.6MPa.

[0012] Specifically, the feeding rate of the sodium hydroxide solution is controlled at 0.1L / min-0.3L / min, the addition amount of the barium chloride solution is calculated according to the sulfate ion content, and the filtration accuracy of the precision filter is 1μm to ensure the clarity of the solution and the absence of impurities.

[0013] Preferably, the lithium carbonate conversion crystallization step uses a sodium carbonate solution with a concentration of ≥30% and a temperature control range of 30°C-40°C.

[0014] Specifically, the feeding rate of the sodium carbonate solution is controlled at 0.2L / min-0.5L / min, and the conversion crystallization time is controlled at 1-3 hours to ensure that the lithium carbonate is fully crystallized and precipitated.

[0015] Preferably, the demagnetization treatment step comprises the following steps: Demagnetization of crude lithium carbonate: Preliminary removal of magnetic substances in lithium carbonate through a magnetic separator; Multi-stage magnetic separation: The content of magnetic substances is further reduced through multi-stage magnetic separation equipment; Ultrafine grinding and demagnetization: Crush the crude lithium carbonate to micron level and use high gradient magnetic separation equipment for deep demagnetization. The magnetic field strength of the magnetic separator is 1.5 Tesla-2.0 Tesla, and the magnetic field strength of the high gradient magnetic separation equipment is 2.5 Tesla-3.0 Tesla.

[0016] Specifically, in the initial demagnetization stage, the operating temperature of the magnetic separator is controlled at room temperature, the magnetic field intensity of the multi-stage magnetic separation equipment increases step by step, and after ultra-fine grinding, demagnetization is performed again through a high-gradient magnetic separation equipment to ensure that the content of magnetic substances is less than 100ppb.

[0017] Preferably, the magnetic field strength of the magnetic separator is not less than 1.5 Tesla to ensure the preliminary demagnetization effect, and the magnetic field strength of the high-gradient magnetic separation equipment is not less than 2.5 Tesla to ensure the deep demagnetization effect.

[0018] Specifically, the working environment humidity of the magnetic separator and high gradient magnetic separation equipment is controlled at 30%-50% to prevent the magnetic material from absorbing moisture and agglomerating, affecting the demagnetization effect.

[0019] Preferably, the product pulverizing step adopts air flow pulverizing equipment to control the particle size of lithium carbonate to 2µm≤D50≤8µm, the air flow velocity range of the air flow pulverizing equipment is 300-500m / s, and the pulverizing pressure range is 0.6MPa-1.0MPa.

[0020] Specifically, the air flow pulverizing equipment uses high-pressure air as the pulverizing medium, and the temperature of the pulverizing chamber is controlled at room temperature to prevent the lithium carbonate particles from overheating and affecting the quality during the pulverizing process.

[0021] Preferably, before the lithium carbonate conversion crystallization step, a complexing agent is added to form a complex with impurity ions to prevent impurities from entering the lithium carbonate crystals. The concentration range of the complexing agent is 0.1 mol / L-0.5 mol / L. The complexing agent is selected from EDTA, citric acid or its salts. The amount of the complexing agent added is 0.01%-0.05% of the lithium-rich solution.

[0022] Specifically, the feeding rate of the complexing agent solution is controlled at 0.1 L / min-0.2 L / min, and the stirring time is controlled at more than 30 minutes to ensure that the impurities are fully complexed to form a complex.

[0023] Preferably, in the refining reaction step, the concentration of the sodium hydroxide solution is controlled at 25%-35% to ensure sufficient precipitation of magnesium ions, and in the refining reaction step, the concentration of the barium chloride solution is controlled at 25%-35% to ensure sufficient precipitation of sulfate ions.

[0024] Specifically, the order of adding sodium hydroxide and barium chloride solution is to add sodium hydroxide first, and then add barium chloride after the reaction is completed. The stirring speed is controlled at 200rpm-300rpm to ensure uniform and sufficient reaction.

[0025] The present invention provides a process for reducing magnetic substances in battery-grade lithium carbonate. It has the following beneficial effects: 1. The present invention effectively removes various impurities in the raw brine, including sediment, suspended matter, colloidal substances and magnetic substances, through optimized multi-layer filtration technology, ion-selective electrically driven membrane separation, refining reaction and multi-stage demagnetization process. Such multi-step fine processing ensures that the produced lithium carbonate products have extremely high purity and consistency, thereby greatly improving the quality of battery-grade lithium carbonate and meeting the strict requirements of high-end lithium battery manufacturing.

[0026] 2. The present invention significantly improves the efficiency and stability of the production process by introducing an imported large flow channel ion exchange membrane stack, an optimized membrane stack combination method and an efficient refining reaction step. The improved process not only reduces equipment blockage and membrane pollution problems, but also reduces the maintenance frequency and cost of the equipment, improves the overall operation stability and production continuity of the production line, and ensures the smooth progress of large-scale industrial production.

[0027] 3. The present invention adopts green and environmentally friendly process means in multiple links, such as fine filtering technology and efficient impurity removal technology, which reduces the pollution to the environment during the production process. Through efficient impurity removal and wastewater treatment technology, the generation and discharge of waste are minimized, and the utilization rate of resources and the environmental protection of the process are improved. Such a design not only meets the requirements of modern industry for environmental protection, but also improves the sustainability of the process, providing a solid foundation for the long-term development of the enterprise. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Please see attached Figure 1 ; Example 1: Lithium carbonate production process using multi-layer filtration and high-efficiency electrodialysis separation Specific steps: Brine pretreatment: Adopt inclined plate and inclined tube sedimentation to reduce brine turbidity to 1.1NTU; Solid particles were removed by plate and frame filter press (filtration pressure 0.5 MPa); Multi-media filtration (coarse sand 1-2mm, fine sand 0.5-1mm, anthracite 0.8-1.2mm) for further purification; Finally, the brine turbidity is further reduced through a security filter (PP filter element, filtration accuracy 5μm).

[0031] Electric driven membrane magnesium and lithium separation: Adopt imported large flow channel ion exchange membrane stack (flow channel width 1mm, baffle thickness 0.3mm) and optimize the baffle combination; Efficient lithium-magnesium separation, lithium recovery rate ≥ 85%, magnesium ion removal rate 95%.

[0032] Refining reaction: Magnesium ion precipitation was performed using 30% sodium hydroxide solution at 55°C; Sulfate ion precipitation was performed using 30% barium chloride solution; After circulating filtration through a plate and frame filter press (filtration pressure 0.5MPa), further filtration is performed through a precision filter (filtration accuracy 5μm); Adjust the acid to pH 6-7.

[0033] Lithium carbonate conversion crystallization: Sodium carbonate solution (concentration 30%) was used, the temperature was controlled at 35°C, and the conversion crystallization time was 2 hours.

[0034] Demagnetization treatment: Preliminary demagnetization through a 1.8 Tesla magnetic separator; Multi-stage magnetic separation equipment (2.7 Tesla) further removes magnetism; Ultra-fine grinding and demagnetization, deep demagnetization through high gradient magnetic separation equipment (3.0 Tesla).

[0035] Product crushing: Air flow crushing equipment (air flow velocity 400m / s, crushing pressure 0.8MPa), particle size is controlled at 2µm≤D50≤8µm.

[0036] Summarize: Through multi-layer filtration and high-efficiency electrodialysis separation technology, the effects of brine pretreatment and magnesium-lithium separation are effectively improved, ensuring the high purity and consistency of lithium carbonate, and improving production efficiency and equipment service life.

[0037] New steps and effects: The use of multi-level filtration technology and optimized electrodialysis membrane stack design significantly reduces the maintenance frequency of the equipment and improves the overall production efficiency. In addition, the optimized refining reaction steps and efficient demagnetization treatment have brought the purity and consistency of the final product to a new level.

[0038] Example 2: Lithium carbonate production process with complexing agent-assisted refining reaction Specific steps: Brine pretreatment: Adopt inclined plate sedimentation to reduce brine turbidity to 1NTU; Solid particles were removed by plate and frame filter press (filtration pressure 0.45 MPa); Multi-media filtration (coarse sand 1-2mm, fine sand 0.5-1mm, anthracite 0.8-1.2mm) for further purification; Finally, the brine turbidity is further reduced by a security filter (PP filter element, filtration accuracy 5μm).

[0039] Electric driven membrane magnesium and lithium separation: Adopt imported large-channel ion exchange membrane stack (channel width 1.2mm, partition thickness 0.25mm) and optimize the partition combination; Efficient lithium-magnesium separation is carried out, with a lithium recovery rate ≥88% and a magnesium ion removal rate of 96%.

[0040] Refining reaction: Magnesium ion precipitation was performed using 30% sodium hydroxide solution at 60°C; Sulfate ion precipitation was performed using 30% barium chloride solution; Add EDTA complexing agent (concentration 0.3 mol / L) and stir for 30 minutes; After circulating filtration through a plate and frame filter press (filtration pressure 0.45MPa), further filtration is performed through a precision filter (filtration accuracy 1μm); Adjust the acid to pH 6.5.

[0041] Lithium carbonate conversion crystallization: Sodium carbonate solution (concentration 32%) was used, the temperature was controlled at 36°C, and the conversion crystallization time was 2.5 hours.

[0042] Demagnetization treatment: Preliminary demagnetization through a 2.0 Tesla magnetic separator; Multi-stage magnetic separation equipment (2.8 Tesla) for further demagnetization; Ultra-fine grinding and demagnetization, deep demagnetization through high gradient magnetic separation equipment (3.1 Tesla).

[0043] Product crushing: Air flow crushing equipment (air flow velocity 420m / s, crushing pressure 0.9MPa), particle size is controlled at 2µm≤D50≤8µm.

[0044] Summarize: By using complexing agents to assist the refining reaction, impurities are effectively removed, the purity of lithium carbonate is improved, and the high quality and stability of the product are ensured.

[0045] New steps and effects: The addition of EDTA chelating agent in the refining reaction step makes the removal of impurities more thorough, significantly improves the purity and quality of lithium carbonate, and ensures the application effect of the product in high-end lithium batteries.

[0046] Example 3: Continuous conversion crystallization lithium carbonate production process Specific steps: Brine pretreatment: Adopt inclined plate and inclined tube sedimentation to reduce brine turbidity to 1.2NTU; Solid particles were removed by plate and frame filter press (filtration pressure 0.5 MPa); Multi-media filtration (coarse sand 1-2mm, fine sand 0.5-1mm, anthracite 0.8-1.2mm) for further purification; Finally, the brine turbidity is further reduced through a security filter (PP filter element, filtration accuracy 5μm).

[0047] Electric driven membrane magnesium and lithium separation: Adopt imported large flow channel ion exchange membrane stack (flow channel width 1mm, baffle thickness 0.3mm) and optimize the baffle combination; Efficient lithium-magnesium separation is carried out, with lithium recovery rate ≥85% and magnesium ion removal rate above 95%.

[0048] Refining reaction: Magnesium ion precipitation was performed using 30% sodium hydroxide solution at 55°C; Sulfate ion precipitation was performed using 30% barium chloride solution; After circulating filtration through a plate and frame filter press (filtration pressure 0.5MPa), further filtration is performed through a precision filter (filtration accuracy 5μm); Adjust the acid to pH 6-7.

[0049] Lithium carbonate conversion crystallization: A continuous conversion crystallizer was used, the sodium carbonate solution concentration was 30%, the temperature was 35°C, and the conversion crystallization time was 1.5 hours.

[0050] Demagnetization treatment: Preliminary demagnetization through a 1.8 Tesla magnetic separator; Multi-stage magnetic separation equipment (2.7 Tesla) further removes magnetism; Ultra-fine grinding and demagnetization, deep demagnetization through high gradient magnetic separation equipment (3.0 Tesla).

[0051] Product crushing: Air flow crushing equipment (air flow velocity 400m / s, crushing pressure 0.8MPa), particle size is controlled at 2µm≤D50≤8µm.

[0052] Summarize: The continuous conversion crystallization process shortens the crystallization time, improves production efficiency, and ensures the high purity of lithium carbonate.

[0053] New steps and effects: The continuous conversion crystallization process is adopted to greatly shorten the conversion crystallization time, improve production efficiency and output, and at the same time ensure the purity and quality of the product.

[0054] Example 4: High-precision multi-stage and multi-level demagnetization lithium carbonate production process Specific steps: Brine pretreatment: Adopt inclined plate sedimentation to reduce brine turbidity to 1.1NTU; Solid particles were removed by plate and frame filter press (filtration pressure 0.5 MPa); Multi-media filtration (coarse sand 1-2mm, fine sand 0.5-1mm, anthracite 0.8-1.2mm) for further purification; Finally, the brine turbidity is further reduced through a security filter (PP filter element, filtration accuracy 5μm).

[0055] Electric driven membrane magnesium and lithium separation: Adopt imported large flow channel ion exchange membrane stack (flow channel width 1.2mm, partition thickness 0.3mm) and optimize the partition combination; Efficient lithium-magnesium separation is carried out, with lithium recovery rate ≥85% and magnesium ion removal rate above 95%.

[0056] Refining reaction: Magnesium ion precipitation was performed using 30% sodium hydroxide solution at 55°C; Sulfate ion precipitation was performed using 30% barium chloride solution; After circulating filtration through a plate and frame filter press (filtration pressure 0.5MPa), further filtration is performed through a precision filter (filtration accuracy 5μm); Adjust the acid to pH 6-7.

[0057] Lithium carbonate conversion crystallization: A sodium carbonate solution with a concentration of 30% was used, the temperature was controlled at 35°C, and the conversion crystallization time was 2 hours.

[0058] Demagnetization treatment: A multi-stage and multi-level demagnetization process is used, with a 1.8 Tesla magnetic separator for preliminary demagnetization; Multi-stage magnetic separation equipment (2.7 Tesla) further removes magnetism; High gradient magnetic separation equipment (3.0 Tesla) for deep demagnetization; Ultra-high gradient magnetic separation equipment (3.5 Tesla) performs final demagnetization.

[0059] Product crushing: Air flow crushing equipment (air flow velocity 400m / s, crushing pressure 0.8MPa), particle size is controlled at 2µm≤D50≤8µm.

[0060] Summarize: The high-precision multi-stage and multi-level demagnetization process effectively reduces the content of magnetic substances in lithium carbonate, ensuring that the product purity reaches higher standards.

[0061] New steps and effects: The multi-stage and multi-level demagnetization process is adopted to further improve the demagnetization effect, significantly reduce the content of magnetic substances in lithium carbonate, ensure the high purity of the product, and meet the needs of high-end applications.

[0062] Example 5: Lithium carbonate production process based on refined process control Specific steps: Brine pretreatment: Adopt inclined plate sedimentation to reduce brine turbidity to 1.1NTU; Solid particles were removed by plate and frame filter press (filtration pressure 0.5 MPa); Multi-media filtration (coarse sand 1-2mm, fine sand 0.5-1mm, anthracite 0.8-1.2mm) for further purification; Finally, the brine turbidity is further reduced through a security filter (PP filter element, filtration accuracy 5μm).

[0063] Electric driven membrane magnesium and lithium separation: Adopt imported large flow channel ion exchange membrane stack (flow channel width 1.2mm, partition thickness 0.3mm) and optimize the partition combination; Efficient lithium-magnesium separation is carried out, with lithium recovery rate ≥85% and magnesium ion removal rate above 95%.

[0064] Refining reaction: Magnesium ion precipitation was performed using 30% sodium hydroxide solution at 55°C; Sulfate ion precipitation was performed using 30% barium chloride solution; After circulating filtration through a plate and frame filter press (filtration pressure 0.5MPa), further filtration is performed through a precision filter (filtration accuracy 5μm); Adjust the acid to pH 6-7.

[0065] Lithium carbonate conversion crystallization: A sodium carbonate solution with a concentration of 30% was used, the temperature was controlled at 35°C, and the conversion crystallization time was 2 hours.

[0066] Demagnetization treatment: Preliminary demagnetization through a 1.8 Tesla magnetic separator; Multi-stage magnetic separation equipment (2.7 Tesla) further removes magnetism; Ultra-high gradient magnetic separation equipment (3.5 Tesla) performs final demagnetization.

[0067] Product crushing: Air flow crushing equipment (air flow velocity 400m / s, crushing pressure 0.8MPa), particle size is controlled at 2µm≤D50≤8µm.

[0068] Summarize: The production process based on refined process control ensures precise control of each step, effectively improving the purity and consistency of lithium carbonate and meeting the requirements of high-end lithium battery manufacturing.

[0069] New steps and effects: Through refined process control, the operating parameters of each step are precisely adjusted and optimized, which further improves the purity and consistency of the product and ensures a stable supply of high-quality lithium carbonate.

[0070] Summary These five embodiments demonstrate different process optimization schemes, from multi-layer filtration and high-efficiency electrodialysis separation, complexing agent-assisted refining reaction, continuous conversion crystallization, high-precision multi-stage and multi-level demagnetization to refined process control, each with its own emphasis and characteristics. Each embodiment has been improved and optimized in different links, solving some key problems in the prior art, such as equipment blockage, low impurity removal efficiency, low production efficiency, etc., to achieve the purpose of improving product purity, reducing impurity content, and improving production efficiency. These embodiments not only provide specific operating steps and equipment parameters, but also demonstrate the advantages of each technical solution, providing a reliable reference for actual production. Through these innovative process designs and optimizations, the present invention has achieved significant technological progress in the production process of battery-grade lithium carbonate.

[0071] Test experiment: Comparison of magnetic material content Testing Process Sample preparation: Production was carried out according to the process steps of Example 1 to Example 5, and the amount of lithium carbonate sample produced in each example was 500 grams.

[0072] Three samples were taken for each example to ensure the reliability and repeatability of the data.

[0073] Test items: Magnetic substance content test: Use ICP-MS (inductively coupled plasma mass spectrometry) instrument to test the content of magnetic substances in lithium carbonate.

[0074] Test method: ICP-MS: After dissolving the sample, the concentration of magnetic substances is analyzed by ICP-MS.

[0075] Test steps: Weigh 10 grams of the lithium carbonate sample produced in each example and dissolve it in an appropriate amount of acid solution.

[0076] The results were analyzed by ICP-MS, and each sample was tested 3 times to obtain the average value.

[0077] Test data and results Magnetic material content test results (unit: ppb) Example Sample 1 Sample 2 Sample 3 average value Example 1 120 115 118 117.67 Example 2 80 78 82 80.00 Example 3 130 128 132 130.00 Example 4 50 52 48 50.00 Example 5 60 62 58 60.00 Test Results Summary Embodiment 1: The average content of magnetic substances is 117.67 ppb.

[0078] Multi-layer filtration and high-efficiency electrodialysis separation technologies are effective in removing impurities, but the content of magnetic substances is relatively high.

[0079] Embodiment 2: The average magnetic material content is 80.00 ppb.

[0080] By using complexing agents to assist the refining reaction, the content of magnetic substances is effectively reduced and the purity of the product is significantly improved.

[0081] Embodiment 3: The average magnetic material content is 130.00 ppb.

[0082] The continuous conversion crystallization process improves production efficiency, but the content of magnetic substances is slightly higher, and the demagnetization process needs to be further optimized.

[0083] Embodiment 4: The average magnetic material content is 50.00 ppb.

[0084] The high-precision multi-stage and multi-level demagnetization process significantly reduces the content of magnetic substances and has the best effect. It is suitable for occasions with extremely high requirements on product quality.

[0085] Embodiment 5: The average magnetic material content is 60.00 ppb.

[0086] Based on refined process control, it has good overall performance and excels in controlling magnetic materials.

[0087] Summary Through the above test experiments, it can be seen that the effect of each embodiment in controlling the content of magnetic substances. The content of magnetic substances in Examples 1 and 3 is relatively high, and the demagnetization process needs to be further optimized. Example 2 effectively reduces the content of magnetic substances by using a complexing agent to assist the refining reaction. Example 4 adopts a high-precision multi-stage and multi-level demagnetization process, which significantly reduces the content of magnetic substances and has the best effect. Example 5 is based on refined process control, has good comprehensive performance, and has excellent magnetic substance control effect.

[0088] Comparative experiment 1: Comparison of impurity removal effects Existing technical solutions: The existing technology uses single-layer filtration and conventional electrodialysis to separate magnesium and lithium, and then removes calcium, magnesium and sulfate impurities through chemical precipitation, and uses conventional magnetic separation equipment for demagnetization.

[0089] Technical solution of the present invention: The invention adopts multi-layer filtration and high-efficiency electrodialysis separation technology, adds a complexing agent to assist precipitation in the refining reaction, and uses multi-stage and multi-level high-precision magnetic separation equipment to perform demagnetization treatment.

[0090] Test Parameters Filtration pressure: 0.3MPa (existing technology), 0.5MPa (present invention) Membrane stack flow channel width: 1.5mm (existing technology), 1mm (present invention) Membrane stack separator thickness: 0.5mm (existing technology), 0.3mm (present invention) Complexing agent: None (prior art), EDTA 0.3 mol / L (present invention) Magnetic field strength: 1.5 Tesla (existing technology), 3.0 Tesla (present invention) Testing Process The brine samples of the same batch are processed respectively according to the prior art and the technology of the present invention.

[0091] Determine the impurity content (calcium, magnesium, sulfate, magnetic substances) in each sample.

[0092] The operating parameters and processing time for each step were recorded.

[0093] Experimental data Technical Solution Magnesium (ppm) Sulfate (ppm) Magnetic substances (ppb) Filtration pressure (MPa) Complexing agent Magnetic Field Strength (Tesla) Total processing time (hours) Prior art 20 30 150 0.3 none 1.5 28 The present invention 3 7 50 0.5 EDTA 3.0 26 Results Analysis The technical solution of the present invention is significantly better than the existing technology in the removal effect of calcium, magnesium, sulfate and magnetic substances, the impurity content is greatly reduced, and the processing time is shorter, which shows that the process of the present invention has significant advantages in impurity removal.

[0094] Comparative experiment 2: Comparison of product purity and consistency Existing technical solutions: The prior art uses conventional precipitation and crystallization methods, performs demagnetization through single-stage magnetic separation equipment, and uses conventional pulverization equipment to pulverize the product.

[0095] Technical solution of the present invention: The invention adopts a high-efficiency precipitation and crystallization method, uses a multi-stage high-precision magnetic separation device for demagnetization, and uses an air flow pulverizing device for product pulverization.

[0096] Test Parameters Precipitation temperature: 40°C (prior art), 55°C (present invention) Crystallization time: 3 hours (prior art), 2 hours (present invention) Magnetic field strength: 1.5 Tesla (existing technology), 3.0 Tesla (present invention) Crushing equipment: conventional crushing (existing technology), air flow crushing (the present invention) Testing Process The same batch of lithium carbonate samples are processed respectively according to the prior art and the technology of the present invention.

[0097] Product purity and consistency were determined for each sample (XRD and TGA).

[0098] The operating parameters and processing time for each step were recorded.

[0099] Experimental data Technical Solution Product purity (%) consistency(%) Precipitation temperature (℃) Crystallization time (hours) Magnetic Field Strength (Tesla) Crushing equipment Total processing time (hours) Prior art 98.5 85 40 3 1.5 Conventional crushing 30 The present invention 99.8 95 55 2 3.0 Air flow crushing 27 Results Analysis The technical solution of the present invention is significantly superior to the existing technology in terms of product purity and consistency, and the processing time is shorter, which shows that the process of the present invention has obvious advantages in product quality and stability.

[0100] Comparative experiment 3: Comparison of production efficiency and environmental impact Existing technical solutions: The existing technology adopts conventional processes to carry out each step of the treatment, uses traditional equipment, has high energy consumption, and produces a lot of wastewater and waste residue.

[0101] Technical solution of the present invention: The present invention adopts optimized high-efficiency technology and uses energy-saving equipment to reduce energy consumption and the generation of waste water and waste residue.

[0102] Test Parameters Energy consumption: Electricity consumption (kWh) Wastewater volume: Discharge volume after treatment (L) Waste residue amount: Discharge amount after treatment (kg) Production efficiency: output per unit time (kg / h) Testing Process Production was carried out according to the prior art and the technology of the present invention, and the energy consumption, waste water and waste residue generated were recorded.

[0103] Calculate production efficiency per unit time.

[0104] Experimental data Technical Solution Power consumption (kWh) Wastewater volume (L) Waste residue amount (kg) Production efficiency (kg / h) Prior art 5000 1500 200 10 The present invention 4000 1000 120 12 Results Analysis The technical solution of the present invention is significantly lower than the prior art in terms of power consumption, wastewater and waste residue generation, and has higher production efficiency, which shows that the process of the present invention has significant advantages in environmental protection and production efficiency.

[0105] Summary Through three complex comparative experiments, it can be seen that the present invention is significantly superior to the prior art in reducing impurity content, improving product purity and consistency, improving production efficiency and reducing environmental impact. These data and results fully demonstrate the superiority of the process of the present invention and provide a reliable reference for actual production.

[0106] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for reducing magnetic substances in battery-grade lithium carbonate, characterized in that: The following steps are involved: The pretreatment of brine adopts inclined plate sedimentation, plate and frame filter press, multi-media filtration and security filtration; Electro-driven membrane magnesium-lithium separation, efficient lithium-magnesium separation through ion-selective electro-driven membrane; Refining reaction, using sodium hydroxide and barium chloride solution to deeply remove calcium, magnesium and sulfate ions; Lithium carbonate conversion crystallization, through sodium carbonate solution conversion crystallization; Demagnetization treatment, using a multi-stage and multi-level demagnetization process to reduce the content of magnetic substances in lithium carbonate; The product is crushed and the particle size of lithium carbonate is controlled by air flow crushing equipment.

2. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 1, characterized in that: The brine pretreatment step comprises: Reduce brine turbidity to 1NTU-1.2NTU through inclined plate and inclined tube sedimentation; The brine turbidity is further reduced through plate and frame filtration, multi-media filtration and security filtration.

3. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 1, characterized in that: The electrically driven membrane magnesium-lithium separation step adopts an imported large flow channel ion exchange membrane stack and optimizes the combination of partitions in the membrane stack to ensure that the lithium recovery rate of magnesium-lithium separation is ≥80%.

4. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 1, characterized in that: The refining reaction step comprises: Magnesium ion precipitation was performed using 30% sodium hydroxide solution at 50-60°C; Sulfate ion precipitation was performed using 30% barium chloride solution; After circulating filtration through a plate and frame filter press, it is filtered through a precision filter and the acid is adjusted to a pH value of 6-7; The filtration pressure range of the plate and frame filter press is 0.3-0.6MPa.

5. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 1, characterized in that: The lithium carbonate conversion crystallization step uses a sodium carbonate solution, and the concentration of the sodium carbonate solution is ≥30%; The temperature control range of the sodium carbonate solution is 30°C-40°C.

6. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 1, characterized in that: The demagnetization treatment step comprises the following steps: Demagnetization of crude lithium carbonate: Preliminary removal of magnetic substances in lithium carbonate through a magnetic separator; Multi-stage magnetic separation: The content of magnetic substances is further reduced through multi-stage magnetic separation equipment; Ultrafine grinding and demagnetization: Crush the crude lithium carbonate to micron level and perform deep demagnetization through high gradient magnetic separation equipment; The magnetic field strength of the magnetic separator is 1.5 Tesla-2.0 Tesla, and the magnetic field strength of the high gradient magnetic separation equipment is 2.5 Tesla-3.0 Tesla.

7. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 6, characterized in that: The magnetic field strength of the magnetic separator is not less than 1.5 Tesla to ensure the preliminary demagnetization effect, and the magnetic field strength of the high-gradient magnetic separation equipment is not less than 2.5 Tesla to ensure the deep demagnetization effect.

8. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 1, characterized in that: The product pulverizing step adopts air flow pulverizing equipment to control the particle size of lithium carbonate to 2µm≤D50≤8µm, the air flow velocity range of the air flow pulverizing equipment is 300-500m / s, and the pulverizing pressure range is 0.6MPa-1.0MPa.

9. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 1, characterized in that: Before the lithium carbonate conversion crystallization step, a complexing agent is added to form a complex with impurity ions to prevent impurities from entering the lithium carbonate crystals. The concentration range of the complexing agent is 0.1 mol / L-0.5 mol / L. The complexing agent is selected from EDTA, citric acid or its salts. The amount of the complexing agent added is 0.01%-0.05% of the lithium-rich solution.

10. A process for reducing magnetic substances in battery-grade lithium carbonate according to claim 1, characterized in that: In the refining reaction step, the concentration of the sodium hydroxide solution is controlled at 25%-35% to ensure sufficient precipitation of magnesium ions. In the refining reaction step, the concentration of the barium chloride solution is controlled at 25%-35% to ensure sufficient precipitation of sulfate ions.

Citation Information

Cited By

  • Method for reducing magnetic substances in battery-grade lithium carbonate

    CN120662445A